Reputation and Risk Management in Promotional Activities in Relation to the Brand Identity of IQOS - Agung Krisprimandoyo, Denpharanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
It aims to reveal the interaction between reputation, risk management, and promotional efforts through conventional and digital forms. It provides an understanding of the IQOS brand identity strategy, insights into the link between reputation management and promotional efforts, and the critical role of strategic communications in shaping. This research used Qualitative methods, such as in-depth interviews and focus group discussions, offer valuable insights into stakeholders' perceptions, attitudes, and emotions related to IQOS's promotional activities. The investigation carried out on the promotional activities of IQOS has revealed intricate observations regarding the brand's reputation and techniques for managing risks. The study employs a comprehensive methodology that includes qualitative approaches, comparative analysis, ethnographic research, case study analysis, and content analysis. Through this complex approach, the study reveals several significant discoveries. This research provides a comprehensive analysis of IQOS, examining the intricate relationship among reputation, risk management, and promotional tactics.